Spatial-temporal patterns of ambient fine particulate matter (PM2.5) and black carbon (BC) pollution in Accra. (25th June 2021) - Alli, Abosede S; Clark, Sierra N; Hughes, Allison; Nimo, James; Bedford-Moses, Josephine; Baah, Solomon; Wang, Jiayuan; Vallarino, Jose; Agyemang, Ernest; Barratt, Benjamin; Beddows, Andrew; Kelly, Frank; et al.
Abstract: Sub-Saharan Africa (SSA) is rapidly urbanizing, and ambient air pollution has emerged as a major environmental health concern in growing cities. Yet, effective air quality management is hindered by limited data. We deployed robust, low-cost and low-power devices in a large-scale measurement campaign and characterized within-city variations in fine particulate matter (PM2.5 ) and black carbon (BC) pollution in Accra, Ghana. Between April 2019 and June 2020, we measured weekly gravimetric (filter-based) and minute-by-minute PM2.5 concentrations at 146 unique locations, comprising of 10 fixed (∼1 year) and 136 rotating (7 day) sites covering a range of land-use and source influences. Filters were weighed for mass, and light absorbance (10 −5 m −1 ) of the filters was used as proxy for BC concentration. Year-long data at four fixed sites that were monitored in a previous study (2006–2007) were compared to assess changes in PM2.5 concentrations. The mean annual PM2.5 across the fixed sites ranged from 26 μ g m −3 at a peri-urban site to 43 μ g m −3 at a commercial, business, and industrial (CBI) site. CBI areas had the highest PM2.5 levels (mean: 37 μ g m −3 ), followed by high-density residential neighborhoods (mean: 36 μ g m −3 ), while peri-urban areas recorded the lowest (mean: 26 μ g m −3 ). Both PM2.5 and BC levels were highest during the dry dusty Harmattan period (mean PM2.5 : 89 μ g m −3 ) compared to non-Harmattan season (mean PM2.5 : 23 μ g m −3 ). PM2.5 at all sites peaked at dawn and dusk, coinciding with morning and evening heavy traffic. We found about a 50% reduction (71 vs 37 μ g m −3 ) in mean annual PM2.5 concentrations when compared to measurements in 2006–2007 in Accra. Ambient PM2.5 concentrations in Accra may have plateaued at levels lower than those seen in large Asian megacities. However, levels are still 2- to 4-fold higher than the WHO guideline. Effective and equitable policies are needed to reduce pollution levels and protect public health.